Factors influencing interprofessional collaboration between community pharmacists and general practitioners—A systematic review - Bollen, Annelies; Harrison, Reema; Aslani, Parisa; van Haastregt, Jolanda C.M. (Health & social care in the community, 2019)
Effective interprofessional collaboration is critical for sustaining high quality care in the context of the increasing burden on primary healthcare services. Despite this, there is limited understanding of the factors contributing to effective collaboration between general practitioners and community pharmacists. The aim of this systematic review was to identify the factors that impact on interprofessional collaboration between general practitioners (GPs) and community pharmacists (CPs). Keywords and synonyms were combined and applied to four databases (EMBASE, CINAHL, SCOPUS, and MEDLINE) to identify articles published between January 2000 to April 2017. Relevant journals and reference lists were also hand‐searched. A total of 37 articles met the eligibility criteria. Factors that posed a challenge to effective interprofessional collaboration were the perceived imbalance in hierarchy and power between the professions and a lack of understanding of each other's skills and knowledge. Experience of collaboration with the other party led to greater understanding of each other's capabilities and potential role in co‐delivering patient care. The physical environment was also identified as important, with co‐location and other resources to facilitate clear and regular communication identified as important facilitators of interprofessional collaboration. The review findings highlight a range of approaches that may positively influence interprofessional collaboration between GPs and CPS such as co‐location, co‐education to understand the professional capabilities of each group, and utilising compatible technologies to facilitate communication between the two professions.